Experimental and numerical analysis of composites reinforced with natural fibers - Moura, Luana Andreza Gomes (2023)
Composites reinforced with natural fibers are a relatively new class of engineering material that can be used in different industrial applications. While synthetic fiber-reinforced polymer composites have traditionally been employed in high-performance structures, the interest in natural fiber-reinforced composites is growing due to their ecological advantages, renewability, and cost-effectiveness. Jute is a natural fiber easily found in Brazil, its use is environment friendly and improves local economies. Natural fibers also present some drawbacks compared to synthetic fibers, such as poor resistance to moisture absorption, random properties, and a hydrophilic behavior, which can be prevented by fiber treatment. This research aims to explore the mechanical behavior of jute-glass hybrid-reinforced epoxy composites through both experimental and numerical analyses. The primary objectives include the production of hybrid composites using manual lamination, the characterization of fundamental mechanical properties of the composites and their constituents, and the development of a numerical model using Hashin’s failure initiation criteria and a damage evolution law based on fracture energy. Experimental tests were conducted on treated and untreated jute fibers, as well as on different jute-glass hybrid composites. Tensile tests and fracture toughness analysis were performed to obtain critical mechanical properties for numerical modeling. The numerical study was carried out using Abaqus software, simulating the behavior of the hybrid composites. The results of the experimental tests demonstrated the feasibility and mechanical properties of the jute-glass hybrid composites. The numerical simulations using the properties from the experimental tests showed good agreement with the experimental findings. Additionally, the numerical model utilizing separate properties for jute and glass exhibited promising results, representing the mechanical behavior of the hybrid composites effectively. Overall, this research provides valuable insights into the mechanical properties and behavior of jute-glass hybrid-reinforced composites. The combination of experimental and numerical analyses offers a comprehensive understanding of the material, facilitating its potential applications. The findings contribute to the ongoing research on natural fiber composites and provide a basis for further optimization and development of hybrid materials with enhanced mechanical performance and eco-friendly attributes.